2007 Microsoft Office system inside out - Boyce, Jim 1958-; Pierce, John 1954- (Inside out, 2007)
Provides timesaving tips, tricks, shortcuts, solutions, and troubleshooting guidelines for Microsoft Access, Excel, Outlook, Word, PowerPoint, and other applications and explores new features and capabilities of Office 2007.